Treatment of vitamin K-dependent coagulation factor deficiency and subarachnoid hemorrhage - Chen, Hai-fei (Second Affiliated Hospital of Zhejiang University School of Medicine, 2011)
BACKGROUND: In adults, vitamin K-dependent coagulation factor deficiency (VKCFD) increases in the recent years. We treated a VKCFD patient with subarachnoid hemorrhage, with favorable outcomes. METHODS: A 19-year-old male student with VKCFD was treated at our hospital. The initial treatment was injection of a large dose of vitamin K and fresh plasma, and then with oral high dose of vitamin K4. RESULTS: At 4 weeks after admission, the focus of hemorrhage subsided, neurological examination was normal, and the patient was discharged. CONCLUSIONS: VKCFD is rare and its diagnosis should be based on the history of the patient and the results of laboratory examinations. A large dose of vitamin K is the first choice of treatment.